Systematic Review and Pooled Meta-analysis of the Current Status of Coronary Revascularization Surgery in Bangladesh (Bangladesh Heart Journal, 2021)
Background: There is no consensus on the role of beating heart coronary artery bypass graft surgery (BECAB) in adult Bangladeshi patients requiring coronary revascularization surgery. We aimed to conduct a systematic review on all literature related to BECAB and/or conventional (CCAB) to determine the comparability of the patient outcomes of BECAB with that of a controlled cohort.Method: We carried out a systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. A meta-analysis was conducted to compare clinical outcomes between the BECAB and CCAB cohorts. Pooled analyses were also performed to determine the incidence rates of any adverse outcomes related to CABG.Results: We observed significantly lower rates of operation time (MD: -52.30, CI: -67.73 to -36.86, p